Magmatic evolution characteristics and heterogeneity of the outer zone of the Emeishan Large Igneous Province: a case study of basalts from the Tianquan and Huayingshan areas - C. C. Li; S. Yang; Z. Y. Lin; Y. P. Jing; Y. Xia; Y. H. Chen; J. T. Liao; C. D. Nie (Australian Journal of Earth Sciences, 2026)

Wild bees occupy temporally stable pollen nutritional niches - Anthony D. Vaudo; Jillian A. Luthy; Eva Lin; Sonja K. Glasser; Anne S. Leonard (Oecologia, 2026)
As bees’ primary source of protein and lipids, pollen is a nutritional resource key to the persistence of wild populations. Because bee taxa may differ in their pollen macronutrient requirements, and pollen is a limited resource that varies chemically across plants, nutritional niches may shape bees’ ecological interactions. To explore whether members of bee communities occupy pollen nutritional niches, we analysed the protein and lipid content of pollen collected by abundant bee subgenera ( Nomadopsis , Melanosmia , Eumelissodes , Pyrobombus ) and observed their pollen-collecting visitation to plant species at a single Sierra Nevada meadow across three years. We compared pollen nutrition and host plant visitation among subgenera, and at the species level within Pyrobombus. Subgenera exhibited clear and temporally consistent separation of pollen load macronutrition each year, achieved by either host-plant fidelity or flexibility when foraging. Pyrobombus species shared a nutritional niche, potentially creating competition for pollen macronutrients among species relieved by their taxonomic flexibility. These results offer some of the first evidence that nutritional niches among wild bee taxa are annually stable and demonstrate how different taxa may forage to achieve nutritional consistency. Relevant to bee conservation, our findings emphasize that a nutritionally diverse array of plants may be required to support wild bee communities.

Matriptase proteolysis selectively drives disassembly and internalization of the claudin-7 complex while preserving E-cadherin - Yu-Ling A. Kao; He-Yu Huang; Yin S. Yu; Nanxi Huang; Ya-Chin Chan; Chen-Ray Lee; Michael D. Johnson; Chen-Yong Lin (Human Cell, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

The learning efficiency of the ant Anoplolepis gracilipes (Hymenoptera: Formicidae) varies with temperature - C.-H. Chan; T.-S. Lin; H.-D. Lin; C.-I. Chiu (Insectes Sociaux, 2026)

Assessing Potential Data Sources for Landscape-scale Terrestrial Biodiversity Indicators - Tom Bradfer-Lawrence; Meriel Harrison; Adham Ashton-Butt; Sophie Bennett; Robin J. Boyd; Ella Browning; Graeme Buchanan; Adam Fraser; Sian E. Green; Robert Hawkes; Becky E. Heath; Pen-Yuan Hsing; et al. (Environmental Management, 2026)

Feasibility of home-based, remotely delivered exercise training to improve physical function in older sepsis survivors: a pilot randomized controlled trial - Yi Lin; Rola S. Zeidan; Rezvan Ghaderpanah; Margaret K. Ohama; Min-Han Jung; Naveen Baskaran; Juan Sarmiento Delgado; Stephen D. Anton; Barbara K. Smith; Christiaan Leeuwenburgh; Fang-Chi Hsu; Philip A. Efron; et al. (GeroScience, 2026)
Sepsis survivors frequently experience post-discharge physical function decline and encounter logistical barriers to participation in traditional outpatient rehabilitation. This pilot study examined the feasibility, safety, and preliminary efficacy of a remotely delivered, home-based exercise program on physical function in older sepsis survivors. In this single-blinded, randomized controlled trial (RCT), sepsis survivors aged ≥ 55 years were randomized to (a) 12 weeks of avatar-guided, progressive exercise training group (EX) or (b) a standard care control group (CO). Primary outcomes were feasibility (retention, adherence) and safety (adverse events), whereas secondary outcomes were changes in the 30-s Sit-to-Stand (30SSTS), 4-Stage Balance Test (4SBT), Timed Up-and-Go (TUG) tests, and Eastern Cooperative Oncology Group/Zubrod's (ECOG/Zubrod) performance status score. Twenty-one participants were randomized to either EX ( n = 10, mean age = 69.6 ± 8.5 years, 40% females) or CO ( n = 11, mean age = 72.3 ± 7.9 years, 45% females). Mean retention was 95% and adherence to exercise training was 76%. Thirty-four adverse events (AEs) occurred (EX = 11; CO = 16; consented but not randomized = 7 events), including four serious AEs that were unrelated to the study. The EX group showed trends toward improvements in lower-extremity strength (30SSTS: 1.14 ± 2.91 repetitions, Cohen’s d = 0.393) and balance (4SBT: 5.07 ± 4.75 s, d = 1.07), whereas the CO group showed no change in balance on the 4SBT (0.01 ± 4.38 s, d = 0.003) and trends toward decline in lower-extremity strength on the 30SSTS (− 0.88 ± 0.99 repetitions, d = − 0.883). TUG performance showed modest trends toward reductions in completion time in both groups (EX: − 1.42 ± 6.58 s, d = − 0.216; CO: − 1.27 ± 2.73 s, d = − 0.466). ECOG/Zubrod scores showed a modest trend toward improvement in the EX group subset. This pilot RCT demonstrated that a 12-week, remotely delivered exercise program was safe and feasible for older sepsis survivors and showed preliminary signals of positive change in lower-extremity strength, balance, and functional status, which warrants testing efficacy in an adequately powered Phase IIb RCT. ClinicalTrials.gov NCT05568511.

Host and Environmental Drivers of Gut Microbiome Variation in Wild Anolis Lizards - Yanileth F. López Tacoaman; Maria Alcivar; Karla Alujević; Leah Bakewell; John David Curlis; Anabarbara Gonzalez; Noah D. Gripshover; Samir Gulati; Renata M. Pirani; Noa Ratia; Daniel Romero; Kelly Lin Wuthrich; et al. (Molecular Ecology, 2026)
Animals maintain close associations with diverse microbiota that inhabit their digestive tracts, and these associations can profoundly affect host physiology and fitness. Gut microbiome composition is shaped by both host traits and environmental factors, yet the relative importance of these forces remains unclear in many taxa, including squamate reptiles (lizards and snakes). To address this gap, we analysed the gut microbiomes of seven species of Anolis lizards in the lowland tropical rainforest of central Panama. We sought to determine how environmental and host species characteristics shaped gut microbiome composition. Specifically, we examined (1) interspecific variation in the anole gut microbiome, (2) the relative roles of environment and host species in shaping gut microbiomes across two study locations, and (3) patterns of phylosymbiosis. We found that host‐related factors (species identity, body size, and phylogenetic distance) were significant predictors of the composition of Anolis gut microbiomes. However, environmental factors, including locality and year of sampling (associated with temperature, humidity, and precipitation), also exerted significant effects. We detected evidence of phylosymbiosis, but this pattern was moderate, possibly due to the strong effect of environmental variation. Our work contributes to the growing body of literature on lizard gut microbiomes by using comparative observations across habitats and species to identify the factors that shape these communities in the wild.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

A stable environmental niche for humans in the southern Levant 70–40 ka - Mahmoud Abbas; Zhongping Lai; Hua Tu; Xianjiao Ou; Paul A. Carling; Penghui Lin; Mohammad Alqudah; Bety S. Al-Saqarat; Ting Qiu; Michael D. Petraglia; Zeljko Rezek; John D. Jansen (Quaternary Science Reviews, 2026)

Contrasting behaviour in geogenic degassing along an active segment of the East Anatolian fault zone (Türkiye) - G. Yüce; W. D'Alessandro; C.C. Fu; F. Italiano; M. İçhedef; H. Elmacı; B. Kürkcüoğlu; B. Kahraman; A. Demirtaş; L.H. Lin; D. Yasin; Ş. Gürboğa; et al. (Applied Geochemistry, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Global Occurrence and Environmental Fate of Microplastics in Stormwater Runoff: Unlock the In-depth Knowledge on Nature-Based Removal Strategies - Van-Hiep Hoang; Minh-Ky Nguyen; Tuan-Dung Hoang; Hoang-Lam Nguyen; Chitsan Lin; Balal Yousaf; Minh Cuong Ha; Vu Khac Hoang Bui; Minh-Thuan Pham; S. Woong Chang; D. Duc Nguyen (Reviews of Environmental Contamination and Toxicology, 2025)

Correction: The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Fetal response to maternal exposures of environmental chemicals: Utility of a four-cell human feto-maternal interface organ-on-chip - Haley L. Moyer; SungJin Kim; Bowie P. Lam; Lauren S. Richardson; Han-Hsuan D. Tsai; Lucie C. Ford; Hsing-Chieh C. Lin; Weihsueh A. Chiu; Ramkumar Menon; Arum Han; Ivan Rusyn (Chemico-Biological Interactions, 2025)

Nicotinamide riboside combined with exercise to treat hypertension in middle-aged and older adults: a pilot randomized clinical trial - Yi Lin; Rola S. Zeidan; Stephanie Lapierre-Nguyen; Hannah M. Costello; Stephen D. Anton; Thomas W. Buford; Demetra D. Christou; Michelle L. Gumz; Christiaan Leeuwenburgh; Christopher R. Martens; Mary M. McDermott; Marie E. Migaud; et al. (GeroScience, 2025)
Aerobic exercise lowers blood pressure (BP) with varying effects in hypertensive adults, potentially due to age-related nicotinamide adenine dinucleotide (NAD) metabolism dysregulation. This pilot randomized clinical trial (RCT) tested the efficacy of combining aerobic exercise with the NAD booster nicotinamide riboside (NR) to enhance BP control. In this double-blinded RCT, 54 sedentary adults (≥ 55 years) with mean daytime systolic BP (SBP) ≥ 130 mmHg were randomized to 6 weeks of 1000 mg/day of NR combined with 3 days/week of supervised 30-min walking exercise (NR + Ex), Placebo combined with the same exercise regimen (PL + Ex), or NR alone (NR). The primary outcome was daytime SBP. Other outcomes included pulse wave velocity (PWV), NAD catabolites, and nighttime BP. The primary comparison was between NR + Ex and PL + Ex. Of 54 participants (mean age 67 years, 61% female), 49 (NR + Ex: n = 15, PL + Ex: n = 16, NR: n = 18) completed all study visits (93% adherence to exercise and 90% to supplementation). NR + Ex (mean change = 5.19 ± 13.2 mmHg) did not reduce SBP more than PL + Ex (− 2.71 ± 10.5 mmHg). NR + Ex (− 0.31 ± 0.77 m/s) showed a trend toward a greater reduction in PWV. Levels of NAD catabolites were higher in NR groups. In a post hoc analysis, NR + Ex showed a trend toward greater nighttime BP reductions (systolic: − 9.6 ± 9.22; diastolic: − 4.51 ± 7.12 mmHg) in participants without antihypertensive medications. NR + Ex was not superior to PL + Ex in reducing BP in hypertensive middle-aged and older. However, trends toward greater nighttime BP reduction in NR + Ex in participants without antihypertensive medication warrant further investigation in a Phase IIb RCT. Graphical Abstract

The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Spinocerebellar Ataxia Type 27B can be Suspected Based on Clinical Phenotype: The Massachusetts General Hospital Ataxia Center Experience - Leigh A. Rettenmaier; Jin Yun Helen Chen; Jason MacMore; Anoopum S. Gupta; Chih-Chun Lin; Christopher D. Stephen; David Pellerin; Bernard Brais; Jeremy D. Schmahmann (The Cerebellum, 2025)

Microplastic characteristics, transport, risks, and remediation in groundwater: a review - Van-Hiep Hoang; Minh-Ky Nguyen; Tuan-Dung Hoang; Nelson Rangel-Buitrago; Chitsan Lin; Minh-Thuan Pham; Minh Cuong Ha; Tan Phong Nguyen; Muhammad Shaaban; S. Woong Chang; D. Duc Nguyen (Environmental Chemistry Letters, 2025)

Retraction notice to ‘Applications of engineered biochar in remediation of heavy metal(loid)s pollution from wastewater: Current perspectives toward sustainable development goals’ [Sci. Total Environ., 926 (2024) 171859] - Thien-Khanh Tran; Loan Huynh; Hoang-Lam Nguyen; Minh-Ky Nguyen; Chitsan Lin; Tuan-Dung Hoang; Nguyen Tri Q. Hung; X. Hoan Nguyen; S. Woong Chang; D. Duc Nguyen (Science of The Total Environment, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Plastic wastes for carbon-based materials: Investigations on recent applications towards environmentally sustainable, carbon dioxide capture and green energy - The-Anh Luu; Van-Giang Le; Van-Anh Thai; Minh-Ky Nguyen; Chitsan Lin; Minh-Thuan Pham; S. Woong Chang; D. Duc Nguyen (Environmental Pollution, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Correction to: Do past and present abiotic conditions explain variation in the nutritional quality of wildflower pollens for bees? - Anthony D. Vaudo; Eva Lin; Jillian A. Luthy; Anne S. Leonard; Eliza M. Grames (Evolutionary Ecology, 2025)

Surgical Parameters During Reverse Shoulder Arthroplasty Predict Post-Surgical Kinematics During the Hand-to-Head Motion - Ajinkya A. Rai; Clarissa M. LeVasseur; Gillian E. Kane; Maria A. Munsch; Christopher J. Como; Alexandra S. Gabrielli; Jonathan D. Hughes; William J. Anderst; Albert Lin (Annals of Biomedical Engineering, 2025)

Cigarette butts in Vietnam's marine environments: From pollution to solutions and prospects - Pham Minh Thuan; Minh-Ky Nguyen; Chitsan Lin; Nelson Rangel-Buitrago; Francois Galgani; S. Woong Chang; D. Duc Nguyen (Science of The Total Environment, 2024)

Do past and present abiotic conditions explain variation in the nutritional quality of wildflower pollens for bees? - Anthony D. Vaudo; Eva Lin; Jillian A. Luthy; Anne S. Leonard; Eliza M. Grames (Evolutionary Ecology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Estimating ambient air pollutant concentrations outside and inside homes in the Subpopulations and Intermediate outcomes in COPD air pollution (SPIROMICS air) cohort - Kipruto Kirwa; Amanda J. Gassett; Coralynn Sack; Laura M. Paulin; Cheryl S. Pirozzi; R. Graham Barr; Prescott G. Woodruff; MeiLan Han; May-Lin Wilgus; Igor Barjaktarevic; Stephen Peters; Nadia N. Hansel; et al. (Environmental Research, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Guyparkeria halophila: Novel cell platform for the efficient valorization of carbon dioxide and thiosulfate into ectoine - E. Huang-Lin; D. Tamarit; R. Lebrero; S. Cantera (Bioresource Technology, 2024)

A review on the characterization of microwave-induced biowaste-derived activated carbons for dye adsorption - T. Kopac; S. D. Lin (International Journal of Environmental Science and Technology, 2024)

Identification of pollution sources in rivers by downstream analysis of low-concentration elements associated with wastewater - H.-C. Lin; P.-Y. Hsieh; G.-S. Wang; D.-W. Wang; T.-H. Wang; Y.-C. Hsu; C.-F. Wu (International Journal of Environmental Science and Technology, 2024)

Associations between follicular fluid trace elements and ovarian response during in vitro fertilization - Rooshna Mohsin; Victor Y. Fujimoto; Aubrey L. Galusha; Patrick J. Parsons; Jenna R. Krall; Celeste D. Butts-Jackson; Evelyn Mok-Lin; Michael S. Bloom (Environmental Research, 2024)

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Enhanced detection of heavy metal ions using Ag nanoparticles and single-walled carbon nanotubes within Cu-based metal-organic frameworks - Gajanan A. Bodkhe; Mayuri S. More; Ahmad Umar; Ahmed A. Ibrahim; Subramanian Siva; Megha A. Deshmukh; Nikesh N. Ingle; Dhammajyot K. Gaikwad; Meng-Lin Tsai; Tibor Hianik; Myunghee Kim; Mahendra D. Shirsat (Journal of Environmental Chemical Engineering, 2024)

RETRACTED: Applications of engineered biochar in remediation of heavy metal(loid)s pollution from wastewater: Current perspectives toward sustainable development goals - Thien-Khanh Tran; Loan Huynh; Hoang-Lam Nguyen; Minh-Ky Nguyen; Chitsan Lin; Tuan-Dung Hoang; Nguyen Tri Q. Hung; X. Hoan Nguyen; S. Woong Chang; D. Duc Nguyen (Science of The Total Environment, 2024)

Analytical methodology for determining the extent of pumped freshwater lenses in recharge-limited, circular islands - Barret L. Kurylyk; Yin-Fang Lin; S. Cristina Solórzano-Rivas; Adrian D. Werner (Advances in Water Resources, 2024)

FDA-approved disulfiram as a novel treatment for aggressive leukemia - Mawar Karsa; Lin Xiao; Emma Ronca; Angelika Bongers; Dayna Spurling; Ayu Karsa; Sandra Cantilena; Anna Mariana; Tim W. Failes; Greg M. Arndt; Laurence C. Cheung; Rishi S. Kotecha; et al. (Journal of Molecular Medicine, 2024)
Acute leukemia continues to be a major cause of death from disease worldwide and current chemotherapeutic agents are associated with significant morbidity in survivors. While better and safer treatments for acute leukemia are urgently needed, standard drug development pipelines are lengthy and drug repurposing therefore provides a promising approach. Our previous evaluation of FDA-approved drugs for their antileukemic activity identified disulfiram, used for the treatment of alcoholism, as a candidate hit compound. This study assessed the biological effects of disulfiram on leukemia cells and evaluated its potential as a treatment strategy. We found that disulfiram inhibits the viability of a diverse panel of acute lymphoblastic and myeloid leukemia cell lines ( n = 16) and patient-derived xenograft cells from patients with poor outcome and treatment-resistant disease ( n = 15). The drug induced oxidative stress and apoptosis in leukemia cells within hours of treatment and was able to potentiate the effects of daunorubicin, etoposide, topotecan, cytarabine, and mitoxantrone chemotherapy. Upon combining disulfiram with auranofin, a drug approved for the treatment of rheumatoid arthritis that was previously shown to exert antileukemic effects, strong and consistent synergy was observed across a diverse panel of acute leukemia cell lines, the mechanism of which was based on enhanced ROS induction. Acute leukemia cells were more sensitive to the cytotoxic activity of disulfiram than solid cancer cell lines and non-malignant cells. While disulfiram is currently under investigation in clinical trials for solid cancers, this study provides evidence for the potential of disulfiram for acute leukemia treatment. Key messages Disulfiram induces rapid apoptosis in leukemia cells by boosting oxidative stress. Disulfiram inhibits leukemia cell growth more potently than solid cancer cell growth. Disulfiram can enhance the antileukemic efficacy of chemotherapies. Disulfiram strongly synergises with auranofin in killing acute leukemia cells by ROS induction. We propose testing of disulfiram in clinical trial for patients with acute leukemia.

Effects of lianas on forest biogeochemistry during their lives and afterlives - Gbadamassi G. O. Dossa; Hong‐Lin Li; Bo Pan; Tial C. Ling; Douglas A. Schaefer; Mareike Roeder; Denis M. Njoroge; Juan Zuo; Liang Song; Bismark Ofosu‐Bamfo; Stefan A. Schnitzer; Rhett D. Harrison; et al. (Global Change Biology, 2024)
Climate change and other anthropogenic disturbances are increasing liana abundance and biomass in many tropical and subtropical forests. While the effects of living lianas on species diversity, ecosystem carbon, and nutrient dynamics are receiving increasing attention, the role of dead lianas in forest ecosystems has been little studied and is poorly understood. Trees and lianas coexist as the major woody components of forests worldwide, but they have very different ecological strategies, with lianas relying on trees for mechanical support. Consequently, trees and lianas have evolved highly divergent stem, leaf, and root traits. Here we show that this trait divergence is likely to persist after death, into the afterlives of these organs, leading to divergent effects on forest biogeochemistry. We introduce a conceptual framework combining horizontal, vertical, and time dimensions for the effects of liana proliferation and liana tissue decomposition on ecosystem carbon and nutrient cycling. We propose a series of empirical studies comparing traits between lianas and trees to answer questions concerning the influence of trait afterlives on the decomposability of liana and tree organs. Such studies will increase our understanding of the contribution of lianas to terrestrial biogeochemical cycling, and help predict the effects of their increasing abundance.

Review on fate, transport, toxicity and health risk of nanoparticles in natural ecosystems: Emerging challenges in the modern age and solutions toward a sustainable environment - Thien-Khanh Tran; Minh-Ky Nguyen; Chitsan Lin; Tuan-Dung Hoang; Thanh-Cong Nguyen; Aasif Mohmad Lone; Akhil Pradiprao Khedulkar; Mohamed S. Gaballah; Jagpreet Singh; W. Jin Chung; D. Duc Nguyen (Science of The Total Environment, 2024)

Synthesis of nano-MgO hybrid SDB hydrophobic catalyst carriers and its adsorption behavior of Fe3+ - Y. Fan; H. R. Peng; C. Li; K. Fu; X. Y. Ren; H. J. Yang; S. D. Lin; C. L. Liu (International Journal of Environmental Science and Technology, 2024)

A review on sterilization methods of environmental decontamination to prevent the coronavirus SARS-CoV-2 (COVID-19 virus): A new challenge towards eco-friendly solutions - Nguyen Trung Hiep; Minh-Ky Nguyen; Huynh Tan Nhut; Nguyen Tri Quang Hung; Nguyen Cong Manh; Chitsan Lin; S. Woong Chang; Myoung Jin Um; D. Duc Nguyen (Science of The Total Environment, 2023)

Occurrence, fate, and potential risk of pharmaceutical pollutants in agriculture: Challenges and environmentally friendly solutions - Minh-Ky Nguyen; Chitsan Lin; Hoang-Lam Nguyen; Nguyen Tri Quang Hung; D. Duong La; X. Hoan Nguyen; S. Woong Chang; W. Jin Chung; D. Duc Nguyen (Science of The Total Environment, 2023)

Ecotoxicity of micro- and nanoplastics on aquatic algae: Facts, challenges, and future opportunities - Minh-Ky Nguyen; Chitsan Lin; Hoang-Lam Nguyen; Van-Giang Le; S. Haddout; Myoung-Jin Um; Soon W. Chang; D. Duc Nguyen (Journal of Environmental Management, 2023)

Cloud condensation nuclei activation properties of Mediterranean pollen types considering organic chemical composition and surface tension effects - A. Casans; F. Rejano; J. Maldonado-Valderrama; J.A. Casquero-Vera; S. Ruiz-Peñuela; B.L. van Drooge; H. Lyamani; A. Cazorla; E. Andrews; Jack J. Lin; F. Mirza-Montoro; D. Pérez-Ramírez; et al. (Atmospheric Environment, 2023)

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

A systematic evidence map for the evaluation of noncancer health effects and exposures to polychlorinated biphenyl mixtures - Laura M. Carlson; Krista Christensen; Sharon K. Sagiv; Pradeep Rajan; Carolyn R. Klocke; Pamela J. Lein; Evan Coffman; Rachel M. Shaffer; Erin E. Yost; Xabier Arzuaga; Pam Factor-Litvak; Alexander Sergeev; et al. (Environmental Research, 2023)

DOK7 Promotes NMJ Regeneration After Nerve Injury - Ethan D. Kosco; Hongyang Jing; Peng Chen; Wen-Cheng Xiong; Ivy S. Samuels; Lin Mei (Molecular Neurobiology, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

The role of copper crystallization and segregation toward enhanced methanol synthesis via CO2 hydrogenation over CuZrO2 catalysts: A combined experimental and computational study - Francielle C.F. Marcos; Raphael S. Alvim; Lili Lin; Luis E. Betancourt; Davi D. Petrolini; Sanjaya D. Senanayake; Rita M.B. Alves; José M. Assaf; Jose A. Rodriguez; Reinaldo Giudici; Elisabete M. Assaf (Chemical Engineering Journal, 2023)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Registered clinical trials investigating treatment of long COVID: a scoping review and recommendations for research - Felicia Ceban; Alexia Leber; Muhammad Youshay Jawad; Mathew Yu; Leanna M. W. Lui; Mehala Subramaniapillai; Joshua D. Di Vincenzo; Hartej Gill; Nelson B. Rodrigues; Bing Cao; Yena Lee; Kangguang Lin; et al. (Infectious Diseases, 2022)

A Brief Educational Intervention to Increase ED Initiation of Buprenorphine for Opioid Use Disorder (OUD) - Utsha G. Khatri; Kathleen Lee; Theodore Lin; Joseph L. D’Orazio; Mitesh S. Patel; Frances S. Shofer; Jeanmarie Perrone (Journal of Medical Toxicology, 2022)

Factors associated with changes in exercise behaviors during the COVID-19 pandemic - Caroline Himbert; Cassandra A. Hathaway; Bailee Daniels; Karen Salas; Anjelica Ashworth; Biljana Gigic; Tengda Lin; Richard Viskochil; Anne C. Kirchhoff; Douglas Grossman; Jennifer Ose; Jonathan Tward; et al. (Cancer Causes & Control, 2022)

HIV, pathology and epigenetic age acceleration in different human tissues - Steve Horvath; David T. S. Lin; Michael S. Kobor; Joseph A. Zoller; Jonathan W. Said; Susan Morgello; Elyse Singer; William H. Yong; Beth D. Jamieson; Andrew J. Levine (GeroScience, 2022)
Epigenetic clocks based on patterns of DNA methylation have great importance in understanding aging and disease; however, there are basic questions to be resolved in their application. It remains unknown whether epigenetic age acceleration (EAA) within an individual shows strong correlation between different primary tissue sites, the extent to which tissue pathology and clinical illness correlate with EAA in the target organ, and if EAA variability across tissues differs according to sex. Considering the outsized role of age-related illness in Human Immunodeficiency Virus-1 (HIV), these questions were pursued in a sample enriched for tissue from HIV-infected individuals. We used a custom methylation array to generate DNA methylation data from 661 samples representing 11 human tissues (adipose, blood, bone marrow, heart, kidney, liver, lung, lymph node, muscle, spleen and pituitary gland) from 133 clinically characterized, deceased individuals, including 75 infected with HIV. We developed a multimorbidity index based on the clinical disease history. Epigenetic age was moderately correlated across tissues. Blood had the greatest number and degree of correlation, most notably with spleen and bone marrow. However, blood did not correlate with epigenetic age of liver. EAA in liver was weakly correlated with EAA in kidney, adipose, lung and bone marrow. Clinically, hypertension was associated with EAA in several tissues, consistent with the multiorgan impacts of this illness. HIV infection was associated with positive age acceleration in kidney and spleen. Male sex was associated with increased epigenetic acceleration in several tissues. Preliminary evidence indicates that amyotrophic lateral sclerosis is associated with positive EAA in muscle tissue. Finally, greater multimorbidity was associated with greater EAA across all tissues. Blood alone will often fail to detect EAA in other tissues. While hypertension is associated with increased EAA in several tissues, many pathologies are associated with organ-specific age acceleration.

An assessment of the health risks associated with shared sanitation: a case study of the community ablution blocks in Durban, South Africa - Preshod S. Ramlal; Johnson Lin; Christopher A. Buckley; Thor Axel Stenström; Isaac D. Amoah (Environmental Monitoring and Assessment, 2022)

A bibliometric review of peripartum cardiomyopathy compared to other cardiomyopathies using artificial intelligence and machine learning - M. Grosser; H. Lin; M. Wu; Y. Zhang; S. Tipper; D. Venter; J. Lu; C. G. dos Remedios (Biophysical Reviews, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

From zero to infinity: Minimum to maximum diversity of the planet by spatio‐parametric Rao’s quadratic entropy - Duccio Rocchini; Matteo Marcantonio; Daniele Da Re; Giovanni Bacaro; Enrico Feoli; Giles M. Foody; Reinhard Furrer; Ryan J. Harrigan; David Kleijn; Martina Iannacito; Jonathan Lenoir; Meixi Lin; et al. (Global Ecology and Biogeography, 2021)
Aim The majority of work done to gather information on the Earth's biodiversity has been carried out using in‐situ data, with known issues related to epistemology (e.g., species determination and taxonomy), spatial uncertainty, logistics (time and costs), among others. An alternative way to gather information about spatial ecosystem variability is the use of satellite remote sensing. It works as a powerful tool for attaining rapid and standardized information. Several metrics used to calculate remotely sensed diversity of ecosystems are based on Shannon’s information theory, namely on the differences in relative abundance of pixel reflectances in a certain area. Additional metrics like the Rao’s quadratic entropy allow the use of spectral distance beside abundance, but they are point descriptors of diversity, that is they can account only for a part of the whole diversity continuum. The aim of this paper is thus to generalize the Rao’s quadratic entropy by proposing its parameterization for the first time. Innovation The parametric Rao’s quadratic entropy, coded in R, (a) allows the representation of the whole continuum of potential diversity indices in one formula, and (b) starting from the Rao’s quadratic entropy, allows the explicit use of distances among pixel reflectance values, together with relative abundances. Main conclusions The proposed unifying measure is an integration between abundance‐ and distance‐based algorithms to map the continuum of diversity given a satellite image at any spatial scale. Being part of the rasterdiv R package, the proposed method is expected to ensure high robustness and reproducibility.

A global collaboration to study intimate partner violence-related head trauma: The ENIGMA consortium IPV working group - Carrie Esopenko; Jessica Meyer; Elisabeth A. Wilde; Amy D. Marshall; David F. Tate; Alexander P. Lin; Inga K. Koerte; Kimberly B. Werner; Emily L. Dennis; Ashley L. Ware; Nicola L. de Souza; Deleene S. Menefee; et al. (Brain Imaging and Behavior, 2021)

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

The conduction velocity-potassium relationship in the heart is modulated by sodium and calcium - D. Ryan King; Michael Entz; Grace A. Blair; Ian Crandell; Alexandra L. Hanlon; Joyce Lin; Gregory S. Hoeker; Steven Poelzing (Pflügers Archiv - European Journal of Physiology, 2021)
The relationship between cardiac conduction velocity (CV) and extracellular potassium (K + ) is biphasic, with modest hyperkalemia increasing CV and severe hyperkalemia slowing CV. Recent studies from our group suggest that elevating extracellular sodium (Na + ) and calcium (Ca 2+ ) can enhance CV by an extracellular pathway parallel to gap junctional coupling (GJC) called ephaptic coupling that can occur in the gap junction adjacent perinexus. However, it remains unknown whether these same interventions modulate CV as a function of K + . We hypothesize that Na + , Ca 2+ , and GJC can attenuate conduction slowing consequent to severe hyperkalemia. Elevating Ca 2+ from 1.25 to 2.00 mM significantly narrowed perinexal width measured by transmission electron microscopy. Optically mapped, Langendorff-perfused guinea pig hearts perfused with increasing K + revealed the expected biphasic CV-K + relationship during perfusion with different Na + and Ca 2+ concentrations. Neither elevating Na + nor Ca 2+ alone consistently modulated the positive slope of CV-K + or conduction slowing at 10-mM K + ; however, combined Na + and Ca 2+ elevation significantly mitigated conduction slowing at 10-mM K + . Pharmacologic GJC inhibition with 30-μM carbenoxolone slowed CV without changing the shape of CV-K + curves. A computational model of CV predicted that elevating Na + and narrowing clefts between myocytes, as occur with perinexal narrowing, reduces the positive and negative slopes of the CV-K + relationship but do not support a primary role of GJC or sodium channel conductance. These data demonstrate that combinatorial effects of Na + and Ca 2+ differentially modulate conduction during hyperkalemia, and enhancing determinants of ephaptic coupling may attenuate conduction changes in a variety of physiologic conditions.

Atrial fibrillation rhythm is associated with marked changes in metabolic and myofibrillar protein expression in left atrial appendage - Julie H. Rennison; Ling Li; Cheryl R. Lin; Beth S. Lovano; Laurie Castel; Sojin Youn Wass; Catherine C. Cantlay; Meghan McHale; A. Marc Gillinov; Reena Mehra; Belinda B. Willard; Jonathan D. Smith; et al. (Pflügers Archiv - European Journal of Physiology, 2021)

Magnesium biofortification of Italian ryegrass (Lolium multiflorum L.) via agronomy and breeding as a potential way to reduce grass tetany in grazing ruminants - Diriba B. Kumssa; J. Alan Lovatt; Neil S. Graham; Sarah Palmer; Rory Hayden; Lolita Wilson; Scott D. Young; R. Murray Lark; Beth Penrose; E. Louise Ander; Russell Thompson; Lin-Xi Jiang; et al. (Plant and Soil, 2020)
Aim Magnesium (Mg) deficiency (known as grass tetany) is a serious metabolic disorder that affects grazing ruminants. We tested whether Mg-fertiliser can increase Mg concentration of Italian ryegrasses ( Lolium multiflorum L.) including a cultivar (cv. Bb2067; ‘Magnet’), bred to accumulate larger concentrations of Mg. Methods Under controlled environment (CE) conditions, three cultivars (cv. Bb2067, cv. Bb2068, cv. RvP) were grown in low-nutrient compost at six fertiliser rates (0–1500 μM MgCl 2 .6H 2 O). Under field conditions, the three cultivars in the CE condition and cv. Alamo were grown at two sites, and four rates of MgSO 4 fertiliser application rates (0–200 kg ha −1 MgO). Multiple grass cuts were taken over two-years. Results Grass Mg concentration increased with increasing Mg-fertiliser application rates in all cultivars and conditions. Under field conditions, cv. Bb2067 had 11–73% greater grass Mg concentration and smaller forage tetany index (FTI) than other cultivars across the Mg-fertiliser application rates, sites and cuts. Grass dry matter (DM) yield of cv. Bb2067 was significantly ( p < 0.05) smaller than cv. Alamo. The effect of Mg-fertiliser rate on DM yield was not significant ( p ≥ 0.05). Conclusions Biofortification of grass with Mg through breeding and agronomy can improve the forage Mg concentration for grazing ruminants, even in high-growth spring grass conditions when hypomagnesaemia is most prevalent. Response to agronomic biofortification varied with cultivar, Mg-fertiliser rate, site and weather. The cost:benefit of these approaches and farmer acceptability, and the impact on cattle and sheep grazing on grasses biofortified with Mg requires further investigation.

Exposure to a high dose of amoxicillin causes behavioral changes and oxidative stress in young zebrafish - Cinara L. Gonçalves; Francine F. P. Vasconcelos; Leticia B. Wessler; Isabela S. Lemos; Gabriela Candiotto; Jaime Lin; Mariane B. D. Matias; Eduardo P. Rico; Emilio L. Streck (Metabolic Brain Disease, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

A System Level Analysis of Coastal Ecosystem Responses to Hurricane Impacts - C. J. Patrick; L. Yeager; A. R. Armitage; F. Carvallo; V. M. Congdon; K. H. Dunton; M. Fisher; A. K. Hardison; J. D. Hogan; J. Hosen; X. Hu; B. Kiel Reese; et al. (Estuaries and Coasts, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Exposure of consumers and farmers to organophosphate and synthetic pyrethroid insecticides in Northern Thailand - Surat Hongsibsong; Tippawan Prapamontol; Jie-Xian Dong; Candace S. Bever; Zhen-Lin Xu; Shirley J. Gee; Bruce D. Hammock (Journal of Consumer Protection and Food Safety, 2019)

Identify a shared neural circuit linking multiple neuropsychiatric symptoms with Alzheimer’s pathology - Xixi Wang; Ping Ren; Mark Mapstone; Yeates Conwell; Anton P. Porsteinsson; John J. Foxe; Rajeev D. S. Raizada; Feng Lin (Brain Imaging and Behavior, 2019)

What Promotes the Recovery of Salt Marsh Infauna After Oil Spills? - J. W. Fleeger; M. R. Riggio; I. A. Mendelssohn; Q. Lin; D. R. Deis; D. S. Johnson; K. R. Carman; S. A. Graham; S. Zengel; A. Hou (Estuaries and Coasts, 2019)

Aeromonas shuberti as a cause of multi‐organ necrosis in internal organs of Nile tilapia, Oreochromis niloticus - C Liu; O Q Chang; D F Zhang; K B Li; F Wang; M H Lin; C B Shi; L Jiang; Q Wang; S M Bergmann (Journal of Fish Diseases, 2018)
A disease with white spots in internal organs of Nile tilapia occurred in Zhanjiang, southern China. Multiple, white nodules, 0.8–2.2 mm in diameter, were scattered throughout the liver, spleen and kidney of diseased fish. Signs of nodules reproduced after artificial infection with the isolated strain. Isolated bacteria were Gram‐negative, facultative anaerobic, motile, short rod‐shaped, with a length of 1.2–2.2 μm. Morphological and biochemical tests, as well as phylogenetic analysis, all strongly indicated that the isolate from tilapia is identical to Aeromonas schubertii ( A. schubertii) which temporary named LF 1708 strain. Antibiotic sensitivity assays showed the LF 1708 is sensitive to 24 of 27 tested antibiotics. Pathogenicity test revealed that the isolate at the dose of 3.75 × 10 6 CFU /g killed 100% of experimental tilapia within 2 days and the dose of 1 × 10 7 CFU /g killed 100% of experimental zebrafish within 1 day. Histopathology of diseased tilapia infected with A. schubertii showed numerous necrotic lesions widely distributed in spleen, liver and kidney, and infiltration with a large number of bacteria. To our knowledge, this was the first report that associated A. schubertii with mortality in tilapia.

A Comparative Placebo-Controlled Clinical Trial of the Efficacy and Safety of Interferon β-1a Formulations for S.C. Administration in Patients with Remitting Multiple Sclerosis: First-Year Results - A. N. Boiko; L. P. Bosenko; V. V. Vasilovskii; L. I. Volkova; M. N. Zakharova; S. V. Kotov; E. V. Lekomtseva; T. I. Negrich; E. V. Parshina; O. P. Patrusheva; S. V. Prokopenko; D. V. Sazonov; et al. (Neuroscience and Behavioral Physiology, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

DNA Barcoding for Identification of Sugarcane Borers in China - J- D Wang; W- Z Wang; Z- L Lin; A Ali; H- Y Fu; M- T Huang; S- J Gao; R Wang (Neotropical Entomology, 2018)

Development of a two-stage washing and biodegradation system to remediate octachlorinated dibenzo-p-dioxin-contaminated soils - J. L. Lin; C. D. Dong; C. W. Chen; S. H. Chen; T. E. Hsieh; C. M. Kao (International Journal of Environmental Science and Technology, 2017)

Controlled Release of Vanadium from a Composite Scaffold Stimulates Mesenchymal Stem Cell Osteochondrogenesis - S. D. Schussler; K. Uske; P. Marwah; F. W. Kemp; J. D. Bogden; S. S. Lin; Treena Livingston Arinzeh (The AAPS Journal, 2017)

Cardiotoxicity Associated with Nicotinamide Phosphoribosyltransferase Inhibitors in Rodents and in Rat and Human-Derived Cells Lines - D. L. Misner; M. A. Kauss; J. Singh; H. Uppal; A. Bruening-Wright; B. M. Liederer; T. Lin; B. McCray; N. La; T. Nguyen; D. Sampath; P. S. Dragovich; et al. (Cardiovascular Toxicology, 2017)

Angiopoietins as serum biomarkers for lymphatic anomalies - Timothy D. Le Cras; Paula S. Mobberley-Schuman; Mary Broering; Lin Fei; Cameron C. Trenor; Denise M. Adams (Angiogenesis, 2017)

Changes in Sympathetic Innervation of Rat Caudal Artery in Experimental Myocardial Infarction. Effect of Semax Peptide - A. M. Gorbacheva; A. B. Berdalin; A. N. Stulova; A. D. Nikogosova; M. D. Lin; S. V. Buravkov; S. A. Gavrilova; V. B. Koshelev (Bulletin of Experimental Biology and Medicine, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Functional Genomic Analysis of the Impact of Camelina (Camelina sativa) Meal on Atlantic Salmon (Salmo salar) Distal Intestine Gene Expression and Physiology - Tyler D. Brown; Tiago S. Hori; Xi Xue; Chang Lin Ye; Derek M. Anderson; Matthew L. Rise (Marine Biotechnology, 2016)

Blockade of CD127 Exerts a Dichotomous Clinical Effect in Marmoset Experimental Autoimmune Encephalomyelitis - Jordon Dunham; Li-Fen Lee; Nikki van Driel; Jon D. Laman; Irene Ni; Wenwu Zhai; Guang-Huan Tu; John C. Lin; Jan Bauer; Bert A. ‘t Hart; Yolanda S. Kap (Journal of Neuroimmune Pharmacology, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Identification of a novel cyprinid herpesvirus 3 genotype detected in koi from the East Asian and South‐East Asian Regions - J Chen; D Chee; Y Wang; G Y Lim; S M Chong; Y N Lin; T Huangfu (Journal of Fish Diseases, 2015)
Cyprinid herpesvirus 3 (Cy HV ‐3) is a highly contagious virus that causes significant morbidity and mortality in common carp Cyprinus carpio L. and considered to be one of the most important pathogens of koi and common carp worldwide. Cyprinid herpesvirus 3 infected consignments imported from East Asian and South‐East Asian regions were identified during quarantine period in Singapore, and virus from a 2005 consignment was successfully isolated in koi fin cells. A combination of sequence analyses and duplex PCR were used to characterize 15 Cy HV ‐3 isolates detected in koi consignments between 2005 and 2011. Sequence analyses of the enlarged 9/5, SphI‐5 and TK gene regions identified both the Asian 1 ( n = 11) and European 4 ( n = 4) genotypes. Duplex PCR analysis of two variable marker regions between ORF 29 and ORF 30 (marker I) as well as ORF 133 and its upstream region (marker II ) revealed viruses of genotypes J (I ++ II + ), U/I (I −− II − ), an intermediate genotype (I ++ II − ) and a novel genotype, I ++ II +Δ , which was identified in viruses from seven different consignments. This novel genotype has a 13‐bp deletion in marker II , while maintaining the I ++ allele of marker I. The I ++ II +Δ genotype may have emerged from East Asian and South‐East Asian regions in recent years.

Overexpression of AT14A confers tolerance to drought stress-induced oxidative damage in suspension cultured cells of Arabidopsis thaliana - Lin Wang; Jie He; Haidong Ding; Hui Liu; Bing Lü; Jiansheng Liang; L. Wang; J. He; H. D. Ding; H. Liu; B. Lü; J. S. Liang (Protoplasma, 2015)

Infections of nervous necrosis virus in wild and cage‐reared marine fish from S outh C hina S ea with unexpected wide host ranges - X D Liu; J N Huang; S P Weng; X Q Hu; W J Chen; Z D Qin; X X Dong; X L Liu; Y Zhou; M Asim; W M Wang; J G He; et al. (Journal of Fish Diseases, 2015)
The concerns about the impact of the nervous necrosis virus ( NNV ) infections in wild fish have been raised. This paper presents the results of quarterly surveys of NNV in wild and cage‐reared marine fish from South China Sea. Samples of 892 wild fish belonging to 69 species and 381 cage‐reared fish belonging to 11 species were collected and were detected by seminested PCR and nested PCR . In the case of seminested PCR , the positive signal was detected in 3.0% and 3.1% samples of wild and cage‐reared fish, respectively. However, by nested RT ‐ PCR , the positive signal was observed in 42.3% and 63.0% samples of wild and cage‐reared fish, respectively. If the fish species were considered, the positive signal was detected in 21.7% and 72.7% species of wild and cage‐reared fish by seminested PCR assay, respectively. However, by nested RT ‐ PCR , the positive signal was observed in 65.2% and 100% species of wild and cage‐reared fish, respectively. The nucleotide sequences of the nested PCR products were determined. Phylogenetic tree showed that all the obtained viral isolates belonged to the red‐spotted grouper nervous necrosis virus ( RGNNV ) genotype. Thirty‐five species of the marine fish were the new hosts of NNV .

Mass mortality associated with a viral‐induced anaemia in cage‐reared large yellow croaker, Larimichthys crocea (Richardson) - W J Xu; Z D Qin; H Shi; N Jiang; Y Zhou; X L Liu; J J Xie; G S Wang; W M Wang; M Asim; L B Zeng; L Lin (Journal of Fish Diseases, 2015)

ICE1 demethylation drives the range expansion of a plant invader through cold tolerance divergence - H. J. Xie; H. Li; D. Liu; W. M. Dai; J. Y. He; S. Lin; H. Duan; L. L. Liu; S. G. Chen; X. L. Song; B. E. Valverde; S. Qiang (Molecular Ecology, 2015)
Cold tolerance adaption is a crucial determinant for the establishment and expansion of invasive alien plants into new cold environments; however, its evolutionary mechanism is poorly understood. Crofton weed ( Ageratina adenophora ), a highly invasive alien plant, is continuously spreading across subtropical areas in China, north‐eastward from the first colonized south‐western tropical regions, through cold tolerance evolution. Close relations between the cold tolerance levels of 34 populations, represented by 147 accessions, and the latitude, extreme lowest temperature, coldest month average temperature, and invasion period have provided direct insight into its cold tolerance divergence. A comparative study of the CBF pathway, associated with the cold tolerance enhancement of cold‐susceptible CBF 1 ‐transgenic plant, among four geographically distinct crofton weed populations revealed that the CBF pathway plays a key role in the observed cold tolerance divergence. Four epialleles of the cold response regulator ICE 1 ranged from 66 to 50 methylated cytosines, representing a 4.4% to 3.3% methylation rate and significantly corresponding to the lowest to highest cold tolerance levels among these different populations. The significant negative relation between the transcription levels of the primary CBF pathway members, except for CBF 2 , and the methylation levels among the four populations firstly demonstrates that the demethylation‐upregulated transcription level of CBF pathway is responsible for this evolution. These facts, combined with the cold tolerance variation and methylation found among three native and two other introduced populations, indicate that the ICE 1‐ demethylated upregulation of cold tolerance may be the underlying evolutionary mechanism allowing crofton weed to expand northward in China.

Genetic variation in estrogen and progesterone pathway genes and breast cancer risk: an exploration of tumor subtype-specific effects - Sarah J. Nyante; Marilie D. Gammon; Jay S. Kaufman; Jeannette T. Bensen; Dan Yu Lin; Jill S. Barnholtz-Sloan; Yijuan Hu; Qianchuan He; Jingchun Luo; Robert C. Millikan (Cancer Causes & Control, 2015)

Accumulation of arsenic in rice plant: a study of an arsenic-contaminated site in Taiwan - S.-C. Lin; T.-K. Chang; W.-D. Huang; H.-S. Lur; G.-S. Shyu (Paddy and Water Environment, 2015)

Characterization of baseline sensitivity and resistance risk of Colletotrichum gloeosporioides complex isolates from strawberry and grape to two demethylation-inhibitor fungicides, prochloraz and tebuconazole - X. F. Xu; T. Lin; S. K. Yuan; D. J. Dai; H. J. Shi; C. Q. Zhang; H. D. Wang (Australasian Plant Pathology, 2014)

Association between herpes zoster and end stage renal disease entrance in chronic kidney disease patients: a population-based cohort study - S.-Y. Lin; J.-H. Liu; H.-C. Yeh; C.-L. Lin; I.-J. Tsai; P.-C. Chen; F.-C. Sung; Y.-F. Yang; C.-C. Huang; D. E. Morisky; Y.-J. Chang; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Nanomedicine for glaucoma: sustained release latanoprost offers a new therapeutic option with substantial benefits over eyedrops - Tina T. Wong; Gary D. Novack; Jayaganesh V. Natarajan; Ching Lin Ho; Hla M. Htoon; Subbu S. Venkatraman (Drug Delivery and Translational Research, 2014)

Characterization, tissue distribution and regulation of neuropeptideY in Schizothorax prenanti - R. Wei; C. Zhou; D. Yuan; T. Wang; F. Lin; H. Chen; H. Wu; Z. Xin; S. Yang; Y. Wang; D. Chen; J. Liu; et al. (Journal of Fish Biology, 2014)
In this study, the full‐length neuropeptide Y ( npy ) complementary (c) DNA was cloned in ya fish Schizothorax prenanti . npy cDNA was composed of 789 nucleotides with a 288 nucleotide open reading frame encoding a protein of 96 amino acids. The deduced amino acid sequences contained a 28 amino acids signal peptide followed by a 36 amino acids mature neuropeptide Y (NPY). The npy mRNA was expressed mainly in the brain and eye as detected by real‐time quantitative polymerase chain reaction RT‐PCR ( rt‐qPCR ). The S. prenanti NPY was detectable from blastulation to hatch, suggesting that npy might be involved in the late embryonic development of S. prenanti . An experiment was conducted to determine the expression profile of npy during feeding of a single meal and during long‐term fasting. The expression level of npy in fed fish was significantly decreased at 0·5, 1·5, 3 and 9 h post‐feeding (hpf) than in fasting fish. Fasting for 14 days induced an increase in npy messenger (m) RNA expression in the brain. Overall, the results suggest that NPY is a conserved peptide that might be involved in the regulation of feeding and other physiological function in S. prenanti .

Characterization of Schizothorax prenanti cgnrhII gene: fasting affects cgnrhII expression - T. Wang; D. Yuan; C. Zhou; F. Lin; H. Chen; H. Wu; R. Wei; Z. Xin; J. Liu; Y. Gao; D. Chen; S. Yang; et al. (Journal of Fish Biology, 2014)
In this study, the role of chicken gonadotropin‐releasing hormone II ( cgnrhII ) in feeding regulation was investigated in Schizothorax prenanti . First, the full‐length S. prenanti cgnrhII cDNA consisted of 693 bp with an open reading frame of 261 bp encoding a protein of 86 amino acids. Next, cgnrhII was widely expressed in the central and peripheral tissues. Last, there were significant changes in cgnrhII mRNA expression in the fasted group compared to the fed group in the S. prenanti hypothalamus during 24 h fasting ( P cgnrhII gene expression presented a significant decrease in the fasted group compared with the fed group ( P cgnrhII mRNA expression level between refed and fed group on day 9 ( P > 0·05). Thus, the results suggest that cGnRH II expression is influenced by fasting and the gene may be involved in feeding regulation in S. prenanti.

Association analysis of 9,560 prostate cancer cases from the International Consortium of Prostate Cancer Genetics confirms the role of reported prostate cancer associated SNPs for familial disease - Craig C. Teerlink; Stephen N. Thibodeau; Shannon K. McDonnell; Daniel J. Schaid; Antje Rinckleb; Christiane Maier; Walther Vogel; Geraldine Cancel-Tassin; Christophe Egrot; Olivier Cussenot; William D. Foulkes; Graham G. Giles; et al. (Human Genetics, 2014)

Effect of aging on inter-joint synergies during machine-paced assembly tasks - Xu Xu; Jin Qin; Robert D. Catena; Gert S. Faber; Jia-Hua Lin (Experimental Brain Research, 2013)

Core–shell magnetite-silica dithiocarbamate-derivatised particles achieve the Water Framework Directive quality criteria for mercury in surface waters - C. B. Lopes; P. Figueira; D. S. Tavares; Z. Lin; A. L. Daniel-da-Silva; A. C. Duarte; J. Rocha; T. Trindade; E. Pereira (Environmental Science and Pollution Research, 2013)

Soluble interleukin‐1 receptor, a potential negative regulator of orange‐spotted grouper Epinephelus coioides interleukin‐1 system - D. Q. Lu; M. Yao; S. B. Yi; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2013)
In this study, the cDNA sequence encoding interleukin‐1 ( Il ‐1) receptor‐like protein of orange‐spotted grouper Epinephelus coioides was obtained. The newly identified sequence was named soluble type I Il ‐1 receptor ( sIl‐1rI ) owing to its structural composition, which had two Ig‐like domains, lack of transmembrane region and the Toll/interleukin‐1 receptor ( TIR ) domain, similar to the brown rat Rattus norvegicus soluble Il‐1rI . In addition, sequence comparison and phylogenetic analysis indicated that E. coioides sequence had a closer relationship with Il‐1rI than Il‐1rII . Real‐time PCR revealed that sil‐1rI mRNA expression presented a process of decrease, restoration and increase in Cryptocaryon irritans ‐infected E. coioides . The negative correlation between Il ‐1β and sil‐1rI mRNA in C. irritans ‐infected head‐kidney implied the potential negative regulatory role of sil‐1rI in E. coioides Il ‐1 system. The leucocytes incubated with lipopolysaccharide or polyriboinosinic polyribocytidylic acid exhibited different expression profiles of sil‐1rI . Recombinant Il ‐1β ( rIl ‐1β) protein was capable of inducing sil‐1rI mRNA under the concentration of 100 ng ml −1 , suggesting that high dosage or excess Il ‐1β would stimulate the expression of sil‐1rI to maintain the homoeostasis of E. coioides Il ‐1 system. For the first time, the role of teleost Il‐1rI in parasite infection has been identified, and soluble Il‐1r was found in fish.

Rural livelihoods and climate variability in Ningxia, Northwest China - Yue Li; D. Conway; Yanjuan Wu; Qingzhu Gao; S. Rothausen; Wei Xiong; Hui Ju; Erda Lin (Climatic Change, 2013)

Outcome of metastatic breast cancer in selected women with or without deleterious BRCA mutations - S. Bayraktar; A. M. Gutierrez-Barrera; H. Lin; N. Elsayegh; T. Tasbas; J. K. Litton; N. K. Ibrahim; P. K. Morrow; M. Green; V. Valero; D. J. Booser; G. N. Hortobagyi; et al. (Clinical & Experimental Metastasis, 2013)

FOXO1-mediated upregulation of pyruvate dehydrogenase kinase-4 (PDK4) decreases glucose oxidation and impairs right ventricular function in pulmonary hypertension: therapeutic benefits of dichloroacetate - Lin Piao; Vaninder K. Sidhu; Yong-Hu Fang; John J. Ryan; Kishan S. Parikh; Zhigang Hong; Peter T. Toth; Erik Morrow; Shelby Kutty; Gary D. Lopaschuk; Stephen L. Archer (Journal of Molecular Medicine, 2013)

HOXB13 is a susceptibility gene for prostate cancer: results from the International Consortium for Prostate Cancer Genetics (ICPCG) - Jianfeng Xu; Ethan M. Lange; Lingyi Lu; Siqun L. Zheng; Zhong Wang; Stephen N. Thibodeau; Lisa A. Cannon-Albright; Craig C. Teerlink; Nicola J. Camp; Anna M. Johnson; Kimberly A. Zuhlke; Janet L. Stanford; et al. (Human Genetics, 2013)

Chronic aspiration shifts the immune response from adaptive immunity to innate immunity in a murine model of asthma - Kuei-Ying Su; Anitra D. Thomas; Jui-Chih Chang; Jason H. Leung; Sean M. Lee; Zoie E. Holzknecht; Mary Lou Everett; W. Michael Foster; Monica Kraft; William Parker; R. Duane Davis; Shu S. Lin (Inflammation Research, 2012)

Tetrapeptide H-Ala-Glu-Asp-Arg-OH Stimulates Expression of Cytoskeletal and Nuclear Matrix Proteins - V. Kh. Khavinson; N. S. Lin’kova; V. O. Polyakova; I. M. Kvetnoy; V. V. Benberin; M. M. D’yakonov; Yu. S. Titkov (Bulletin of Experimental Biology and Medicine, 2012)

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

Identification and expression analysis of major histocompatibility complex IIB gene in orange‐spotted grouper Epinephelus coioides - D. Q. Lu; S. B. Yi; M. Yao; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2012)
In this study, complementary DNA (cDNA) and DNA sequences of major histocompatibility complex (MHC) class IIB genes ( mhcIIB ) were cloned from orange‐spotted grouper Epinephelus coioides . The gene structure of E. coioides mhcIIB consists of five exons and four introns, and its deduced amino acid sequence length is 249 amino acids, including a signal peptide, a peptide‐binding region, an IGC1 domain, a transmembrane region and a cytoplasmic tail. A phylogenetic study showed that E. coioides mhcIIB shared 32·0–79·1% identity with those of other teleosts and mammals. Real‐time reverse transcriptase (RT)‐PCR was performed to detect the class IIB gene expression in eight different tissues. To characterize the relationship between E. coioides mhcIIB gene and pathogens, in vivo and in vitro studies were performed. Challenge of Cryptocaryon irritans revealed that class IIB genes were down‐regulated after 24 and 48 h of challenge, and their expression was later restored at 72 h. Stimulation of isolated E. coioides leukocytes with lipopolysaccharide (LPS) and polyinosinic:polycytidylic acid (PolyI:C) significantly increased peripheral blood and spleen mhcIIB expression, while head kidney mhcIIB expression remained constant.

Metabolic imaging of mild traumatic brain injury - A. P. Lin; H. J. Liao; S. K. Merugumala; S. P. Prabhu; W. P. Meehan; B. D. Ross (Brain Imaging and Behavior, 2012)

Germ cells and fertilization differences among Japanese flounder Paralichthys olivaceus , summer flounder Paralichthys dentatus and their first and second generations - J. Sui; D. Y. Ma; Q. H. Liu; S. H. Xu; Z. Z. Xiao; F. Lin; Y. S. Xiao; J. Li (Journal of Fish Biology, 2012)
The morphology of gametes and the fertilization biology of Japanese flounder Paralichthys olivaceus (Po), summer flounder Paralichthys dentatus (Pd) and their hybrids were examined. Multiple generations (two hybrids: Po♀× Pd♂ (F1) and Pd♀× Po♂; two backcrosses: F1♀× Po♂ and F1♀× Pd♂) were obtained by artificial insemination. Comparison of egg ultrastructure among Po, Pd and F1 showed the morphology of micropyle region and the distribution density of pores were species specific. There were c . 100–200 accessory openings around the micropyle in Po, but not in Pd and F1. The zona radiata thickness and number of parallel bands were similar between F1 and Po, which were different from Pd. Comparison of spermatozoa ultrastructure revealed a close relationship between Po and Pd. Cytologically, the six crosses obeyed normal fertilization and cleavage processes, and only one male pronucleus was observed in a fertilized egg, indicating a monospermic fertilization pattern. Analysis of the time distribution from fertilization to first cleavage revealed an obvious delay at pronucleus fusion in the Pd × Po cross. The delay might indicate some cytoplasmic‐nuclear incompatibility during the process of fertilization.

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

A multivalent vaccine for type 1 diabetes skews T cell subsets to Th2 phenotype in NOD mice - Ming S. Lin; Hubert M. Tse; Meghan M. Delmastro; Suzanne Bertera; Caterina T. Wong; Robert Lakomy; Jing He; Martha M. Sklavos; Gina M. Coudriet; Massimo Pietropaolo; Massimo M. Trucco; Jon D. Piganelli (Immunologic Research, 2011)

Learning Through Service: Student Perceptions on Volunteering at Interprofessional Hepatitis B Student-run Clinics - Leslie C. Sheu; Patricia Zheng; Anabelle D. Coelho; Lisa D. Lin; Patricia S. O’Sullivan; Bridget C. O’Brien; Albert Y. Yu; Cindy J. Lai (Journal of Cancer Education, 2011)

Ecological Restoration of Polluted Plain Rivers Within the Haihe River Basin in China - W. Wang; X. Q. Tang; S. L. Huang; S. H. Zhang; C. Lin; D. W. Liu; H. J. Che; Q. Yang; Miklas Scholz (Water, Air, & Soil Pollution, 2010)

Cultivation‐independent characterization of ‘ Candidatus Magnetobacterium bavaricum’ via ultrastructural, geochemical, ecological and metagenomic methods - C. Jogler; M. Niebler; W. Lin; M. Kube; G. Wanner; S. Kolinko; P. Stief; A. J. Beck; D. de Beer; N. Petersen; Y. Pan; R. Amann; et al. (Environmental Microbiology, 2010)
Summary ‘ Candidatus Magnetobacterium bavaricum’ is unusual among magnetotactic bacteria (MTB) in terms of cell size (8–10 µm long, 1.5–2 µm in diameter), cell architecture, magnetotactic behaviour and its distinct phylogenetic position in the deep‐branching Nitrospira phylum. In the present study, improved magnetic enrichment techniques permitted high‐resolution scanning electron microscopy and energy dispersive X‐ray analysis, which revealed the intracellular organization of the magnetosome chains. Sulfur globule accumulation in the cytoplasm point towards a sulfur‐oxidizing metabolism of ‘ Candidatus M. bavaricum’. Detailed analysis of ‘ Candidatus M. bavaricum’ microhabitats revealed more complex distribution patterns than previously reported, with cells predominantly found in low oxygen concentration. No correlation to other geochemical parameters could be observed. In addition, the analysis of a metagenomic fosmid library revealed a 34 kb genomic fragment, which contains 33 genes, among them the complete rRNA gene operon of ‘ Candidatus M. bavaricum’ as well as a gene encoding a putative type IV RubisCO large subunit.

A note on reviving the Goddard Satellite-based Surface Turbulent Fluxes (GSSTF) dataset - Chung-Lin Shie; Long S. Chiu; Robert Adler; Eric Nelkin; I. -I. Lin; Pingping Xie; Feng-Chin Wang; R. Chokngamwong; William Olson; D. Allen Chu (Advances in Atmospheric Sciences, 2009)

Identification of three immunodominant regions on leukotoxin protein of Fusobacterium necrophorum - D. B. Sun; R. Wu; G. L. Li; J. S. Zheng; X. P. Liu; Y. C. Lin; D. H. Guo (Veterinary Research Communications, 2009)

The importance of myocardial amino acids during ischemia and reperfusion in dilated left ventricle of patients with degenerative mitral valve disease - A. Venturini; R. Ascione; H. Lin; E. Polesel; G. D. Angelini; M.-S. Suleiman (Molecular and Cellular Biochemistry, 2009)

Intercomparison, interpretation, and assessment of spring phenology in North America estimated from remote sensing for 1982–2006 - MICHAEL A. WHITE; KIRSTEN M. De BEURS; KAMEL DIDAN; DAVID W. INOUYE; ANDREW D. RICHARDSON; OLAF P. JENSEN; JOHN O'KEEFE; GONG ZHANG; RAMAKRISHNA R. NEMANI; WILLEM J. D. Van LEEUWEN; JESSLYN F. BROWN; ALLARD De WIT; et al. (Global Change Biology, 2009)
Shifts in the timing of spring phenology are a central feature of global change research. Long‐term observations of plant phenology have been used to track vegetation responses to climate variability but are often limited to particular species and locations and may not represent synoptic patterns. Satellite remote sensing is instead used for continental to global monitoring. Although numerous methods exist to extract phenological timing, in particular start‐of‐spring (SOS), from time series of reflectance data, a comprehensive intercomparison and interpretation of SOS methods has not been conducted. Here, we assess 10 SOS methods for North America between 1982 and 2006. The techniques include consistent inputs from the 8 km Global Inventory Modeling and Mapping Studies Advanced Very High Resolution Radiometer NDVIg dataset, independent data for snow cover, soil thaw, lake ice dynamics, spring streamflow timing, over 16 000 individual measurements of ground‐based phenology, and two temperature‐driven models of spring phenology. Compared with an ensemble of the 10 SOS methods, we found that individual methods differed in average day‐of‐year estimates by ±60 days and in standard deviation by ±20 days. The ability of the satellite methods to retrieve SOS estimates was highest in northern latitudes and lowest in arid, tropical, and Mediterranean ecoregions. The ordinal rank of SOS methods varied geographically, as did the relationships between SOS estimates and the cryospheric/hydrologic metrics. Compared with ground observations, SOS estimates were more related to the first leaf and first flowers expanding phenological stages. We found no evidence for time trends in spring arrival from ground‐ or model‐based data; using an ensemble estimate from two methods that were more closely related to ground observations than other methods, SOS trends could be detected for only 12% of North America and were divided between trends towards both earlier and later spring.

An Atlas of ShakeMaps and population exposure catalog for earthquake loss modeling - Trevor I. Allen; David J. Wald; Paul S. Earle; Kristin D. Marano; Alicia J. Hotovec; Kuowan Lin; Michael G. Hearne (Bulletin of Earthquake Engineering, 2009)

Prevalence of helminths in water buffaloes in Hunan Province, China - Y. Liu; F. Li; W. Liu; R. S. Dai; Y. M. Tan; D. S. He; R. Q. Lin; X. Q. Zhu (Tropical Animal Health and Production, 2009)

A quick and efficient approach for gene silencing by using triple putative microRNA-based short hairpin RNAs - Z. X. Shan; Q. X. Lin; M. Yang; C. Y. Deng; S. J. Kuang; Z. L. Zhou; D. Z. Xiao; X. Y. Liu; S. G. Lin; X. Y. Yu (Molecular and Cellular Biochemistry, 2009)

Mapping chromosomal regions affecting flowering time in a spring wheat RIL population - F. Lin; S. L. Xue; D. G. Tian; C. J. Li; Y. Cao; Z. Z. Zhang; C. Q. Zhang; Z. Q. Ma (Euphytica, 2008)

Effect of low-intensity laser radiation of the red spectrum on some properties of erythrocytes in Wistar rats - N. S. Lin’kova; O. P. Gorshkova; V. N. Shuvaeva; D. P. Dvoretskii (Bulletin of Experimental Biology and Medicine, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Health behaviors of cancer survivors: data from an Australian population-based survey - Elizabeth G. Eakin; Danny R. Youlden; Peter D. Baade; Sheleigh P. Lawler; Marina M. Reeves; Jane S. Heyworth; Lin Fritschi (Cancer Causes & Control, 2007)

Livestock Odour Dispersion as Affected by Natural Windbreaks - X.-J. Lin; S. Barrington; J. Nicell; D. Choinière; S. King (Water, Air, & Soil Pollution, 2007)

Apoptosis-dependent and -independent mechanisms mediate the phagocytic recognition/clearance of the HL60-A1 transfectants with prolonged survival - C.-L. Chou; L.-L. Chiang; C.-T. Yu; H.-C. Chen; K.-Y. Lee; S.-M. Lin; C.-D. Huang; W.-T. Liu; P.-C. Chou; C.-H. Wang; H.-C. Lin; H.-P. Kuo; et al. (Inflammation Research, 2007)

Mitochondrial DNA phylogeography of Glyptothorax fokiensis and Glyptothorax hainanensis in Asia - X.‐L. Chen; T.‐Y. Chiang; H.‐D. Lin; H.‐S. Zheng; K.‐T. Shao; Q. Zhang; K.‐C. Hsu (Journal of Fish Biology, 2007)
Whole mitochondrial DNA cytochrome b sequences in 62 fish from 13 locations in Southeast China identified two major clades corresponding to two allopatric taxa, Glyptothorax fokiensis fokiensis and Glyptothorax fokiensis hainanensis . Reciprocal monophyly and a molecular clock separation between these two taxa of 2·3 million years indicate these taxa should be elevated to species. Mismatch distributions and Fu’s F S statistic suggest that both G. fokiensis and G. hainanensis have experienced recent population expansions. Analysis of molecular variance indicates that most of the genetic variation resides among populations within both species, with Φ ST = 0·645 for G. fokiensis and 0·801 for G. hainanensis , suggesting restricted gene flow among populations. Significant correlations between the geographic and the genetic distances provide support for the importance of geographic isolations between populations. Nested clade analysis also confirms low levels of genetic exchanges between the two major groups and between populations within each group. The phylogeographical pattern among populations of Glyptothorax in East Asia can be attributed to historical fragmentations, demographic expansions and occasional long‐distance dispersals stimulated by tectonic activity and Ice Age climate changes.

Characterizing the severe turbulence environments associated with commercial aviation accidents. A real-time turbulence model (RTTM) designed for the operational prediction of hazardous aviation turbulence environments - M. L. Kaplan; J. J. Charney; K. T. Waight; K. M. Lux; J. D. Cetola; A. W. Huffman; A. J. Riordan; S. D. Slusser; M. T. Kiefer; P. S. Suffern; Y.-L. Lin (Meteorology and Atmospheric Physics, 2006)

Climatic Change, Wars and Dynastic Cycles in China Over the Last Millennium - David D. Zhang; C. Y. Jim; George C-S Lin; Yuan-Qing He; James J. Wang; Harry F. Lee (Climatic Change, 2006)

Potential Volatile Organic Compound Exposure from Dry Process Photocopiers in Operation-Idle Mode - D.-J. Hsu; H.-L. Huang; H.-Y. Lin; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2006)

Nucleotide sequence and mRNA expression analysis of β-actin gene in the orange-spotted grouper Epinephelus coioides - W. M. Zhang; Y. Zhang; L. H. Zhang; S. G. Wang; T. Y. Zhu; D. Lin; G. Z. Ma (Fish Physiology and Biochemistry, 2005)

Potential Exposure to VOCs Caused by Dry Process Photocopiers: Results From a Chamber Study - D.-J. Hsu; H.-L. Huang; C.-H. Chien; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2005)

Manganese Uptake and Accumulation by Two Populations of Phytolacca acinosa Roxb. (Phytolaccaceae) - S. G. Xue; Y. X. CHEN; A. J. M. Baker; R. D. Reeves; X. H. Xu; Q. Lin (Water, Air, & Soil Pollution, 2005)

Mapping QTL associated with resistance to Fusarium head blight in the Nanda2419נWangshuibai population. I. TypeII resistance - F. Lin; Z. X. Kong; H. L. Zhu; S. L. Xue; J. Z. Wu; D. G. Tian; J. B. Wei; C. Q. Zhang; Z. Q. Ma (Theoretical and Applied Genetics, 2004)

Natural frequency assessment of stability of root keeper magnetic devices - H. -M. Huang; D. -Z. Liu; Y. -Y. Shiau; C. -Y. Yeh; C. -T. Lin; S. -Y. Lee (Medical & Biological Engineering & Computing, 2004)

Prospective study of serum retinol, β-carotene, β-cryptoxanthin, and lutein/zeaxanthin and esophageal and gastric cancers in China - Christian C. Abnet; You-Lin Qiao; Sanford M. Dawsey; Dennis W. Buckman; Chung S. Yang; William J. Blot; Zhi-Wei Dong; Philip R. Taylor; Steven D. Mark (Cancer Causes & Control, 2003)

Lactococcus garvieae , a cause of disease in grey mullet, Mugil cephalus L., in Taiwan - S‐C Chen; L‐L Liaw; H‐Y Su; S‐C Ko; C‐Y Wu; H‐C Chaung; Y‐H Tsai; K‐L Yang; Y‐C Chen; T‐H Chen; G‐R Lin; S‐Y Cheng; et al. (Journal of Fish Diseases, 2002)

Sphingolipids as biomarkers of fumonisin exposure and risk of esophageal squamous cell carcinoma in China - Christian C. Abnet; Craig B. Borkowf; You-Lin Qiao; Paul S. Albert; Elaine Wang; Alfred H. Merrill; Steven D. Mark; Zhi-Wei Dong; Philip R. Taylor; Sanford M. Dawsey (Cancer Causes & Control, 2001)

Assessing Landscape Condition Relative to Water Resources in the Western United States: A Strategic Approach - K. Bruce Jones; Daniel T. Heggem; Timothy G. Wade; Anne C. Neale; Donald W. Ebert; Maliha S. Nash; Megan H. Mehaffey; Karl A. Hermann; Anthony R. Selle; Scott Augustine; Iris A. Goodman; Joel Pedersen; et al. (Environmental Monitoring and Assessment, 2000)

Agricultural Chemicals in the Alluvial Aquifer of a Typical County of the Arkansas Delta - H. S. Lin; H. D. Scott; K. F. Steele; H. I. Inyang (Environmental Monitoring and Assessment, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

A detailed characterization of the effects of four cannabinoid agonists on operant lever pressing - D. Carriero; J. Aberman; S. Y. Lin; A. Hill; A. Makriyannis; J. D. Salamone (Psychopharmacology, 1998)

Pre- and Postnatal Exposure to 3,3',4,4'-Tetrachlorobiphenyl: II. Effects on the Reproductive Capacity and Fertilizing Ability of Eggs in Female Mice - A. Huang; S. Lin; R. Inglis; D. Powell; K. Chou (Archives of Environmental Contamination and Toxicology, 1998)

Estimation of myocardial glucose utilisation with PET using the left ventricular time-activity curve as a non-invasive input function - X. Li; D. Feng; K. -P. Lin; S. -C. Huang (Medical & Biological Engineering & Computing, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

A high resolution numerical study of Gulf of Mexico fronts and eddies - D. E. Dietrich; C. A. Lin; A. Mestas-Nunez; D. S. Ko (Meteorology and Atmospheric Physics, 1997)

The skin, tongue, and brain as favorable organs for hog cholera diagnosis by immunofluorescence - I. C. Pan; T. S. Huang; C. H. Pan; Shenq-Yi Chern; Shu-Hwae Lee; Y. L. Lin; B. Y. Huang; C. C. Lin; N. J. Li; J. P. Lin; Y. H. Yang; S. Y. Chiu; et al. (Archives of Virology, 1993)